Linguagens documentais para as bibliotecas escolares: o caso da Espanha, Portugal e Brasil - Agustín-Lacruz, María del Carmen (2014)
This article analyzes the specific features and processes of indexing and classification performed in school libraries to process and retrieve information from their collections. Subject languages used in Spanish, Portuguese and Brazilian Portuguese school libraries are also analyzed. To achieve this goal, the concept of school library was analyzed, its function was studied and the techniques and tools that allow the information organization were examined. Among the tools, we studied the Subject Headings Lists for children and juveniles'books and the Subject Headings List for public libraries, the Universal Decimal Classification System (paperback edition) or the classification by fields of interest and specialized thesauri like the Tesauro de la Educacion UNESCO-OIE and the TesauroEuropeo de la Educacion.